Determination of Physicochemical Properties of River Sediment and Heavy Metal Content from River Benue in Ibi, Taraba State - Goodness, Ogbonna (African Journal of Biochemistry and Molecular Biology Research, 2025)
This study assessed contamination levels, potential ecological risks, and pollutant sources of five heavy metals (HMs) in sediments of the River Benue within Ibi Local Government Area, Taraba State, Nigeria. Sediment samples were collected and analyzed for physicochemical properties and trace metal concentrations, including total hydrocarbon content (THC), cadmium (Cd), nickel (Ni), lead (Pb), and zinc (Zn). The results showed that the mean concentrations of the analyzed heavy metals and THC were below the permissible limits established by Nigerian regulatory standards. Similarly, physicochemical parameters—such as pH, electrical conductivity (EC), nitrate, total hydrogen content, sulphate, phosphate, and temperature—were within acceptable environmental limits. Pollution assessment indices, including the Enrichment Factor (EF), Pollution Load Index (PLI), and Geo-accumulation Index (Igeo), indicated low contamination levels, with values generally falling within World Health Organization (WHO) guidelines. Despite these low levels, the study suggests that anthropogenic activities in the region, such as agriculture, domestic discharge, and informal mining, may contribute to the presence of toxic substances in the sediments. The study warns that prolonged exposure to untreated water from this site poses potential health risks. Therefore, continuous environmental monitoring and pollution mitigation strategies are recommended to prevent future ecological degradation and associated public health concerns.